The Impact of a Workweek Reduction on Labor Productivity - Yoonsoo Park; Wooram Park (Korea Development Institute (KDI), 2017)
- Estimating the causal effect of the standard 40-hour workweek policy (2004-11) on the annual output per worker showed an increase of 1.5% at manufacturing establishments with 10-plus employees. - The policy reduced the standard workweek from 44 to 40 hours and was gradually implemented in establishments according to size and industry. - Tentative but suggestive evidence was found that the potential mechanism through which the output per worker increased was owed to the improved efficiency in the production process rather than to the growth in capital input, implying that working hours were inefficiently long before the reduction. - Future policies aiming to reduce working hours should focus on identifying and amending systems and incentive mechanisms that promote inefficient overtime. - Current laws related to maximum working hours and overtime premiums are ambiguous and thus need to be clarified. - Wage structures should be revised to encourage employees to work more efficiently, in a shorter time. Specifically, worker compensation should be based on output (e.g. performance) rather than input (e.g. working hours) and the current high level of the overtime premium should be adjusted.
Keywords: 330